Echocardiographic diagnosis of heart failure with preserved ejection fraction in elderly patients with hypertension. (31st December 2022) - Johansson, Magnus C.; Rosengren, Annika; Fu, Michael
Abstract: Objectives . The aim of this study is to evaluate the diagnostic performance of echocardiography for the diagnosis of heart failure with preserved ejection fraction (HFpEF) in the elderly and to validate the Heart Failure Association diagnostic algorithm (HFA-PEFF). Design. A case–control study was conducted in patients with hypertension with or without HFpEF who were matched for age ( n  = 33; 78.4 ± 5.3 years) and sex. Participants underwent echocardiography including assessment of left atrial (LA) volume index (LAVI), early mitral filling to early diastolic mitral annulus velocity ratio ( E / e ′), LA reservoir strain (LASr), tissue Doppler LA contraction ( a ′), right ventricular isovolumic relaxation time (RVIVRT), and a 6-minute walk test (6-MWT). The filling pressure algorithm from the European association of cardiovascular imaging (EACVI) 2021 was applied. The HFA-PEFF score was also applied, using echocardiography parameters and the value of NT pro-BNP, without considering symptomatic status. Results. Echocardiographic parameters identified patients with HFpEF with an area under the curve (AUC) >0.9 for E / e ′, RVIVRT, LASr, a ′, and the ratio of LAVI/ a ′. LASr correlated with 6-MWT ( r  = 0.59, p  = .0003). The EACVI algorithm classified all controls with normal filling pressure and 94% of patients with HFpEF with increased filling pressure. When the HFA-PEFF diagnostic algorithm was validated, a high score (≥5 points) had 100% sensitivity for HFpEF, while 88% of controls had intermediate scores (2–4 points). Conclusion . The EACVI filling pressure algorithm, RVIVRT, LASr, and the ratio LAVI/ a ′ were accurate for diagnosing HFpEF in elderly patients with hypertension. The HFA-PEFF score had high sensitivity but limited ability to exclude HFpEF.